TEACHER COMMUNICATION PATTERNS TO IMPROVE STUDENTS' RELIGIOUS CHARACTER VALUES AT VOCATIONAL SCHOOLS - Achmad Husaen Sastra Negara; Waston Waston; Syamsul Hidayat; Meti Fatimah; Ahmadi Abdul Adzim; Muhammad Zakir Husain (Profetika: Jurnal Studi Islam, 2023)
This study aims to determine teacher communication patterns in developing students' religious character. This study used a qualitative method with research subjects at SMK IT Ihsanul Fikri Magelang. Data was taken through observation, structured interviews and documentation. The process of systematically searching for and compiling data obtained from interviews, field notes, and other materials is analyzed using steps according to Miles and Huberman including data collection, data presentation, data reduction and conclusion. The results show that the teacher's communication pattern in the development of religious character is that the students of SMKI Ihsanul Fikri have different characteristics and come from different family backgrounds, but over time and the concept of thinking that has been built at SMK IT Ihsanul Fikri, students have understood the importance of religious character so that it needs to be emphasized in everyday life, the next day the teacher's communication pattern in developing religious character is by a) Building an open communication pattern, b) Building cooperation to create effective communication in developing religious character.